2007
DOI: 10.1103/physrevlett.99.224101
|View full text |Cite
|
Sign up to set email alerts
|

Selective Amplification of Scars in a Chaotic Optical Fiber

Abstract: In this letter we propose an original mechanism to select scar modes through coherent gain amplification in a multimode D-shaped fiber. More precisely, we numerically demonstrate the selective amplification of scar modes by positioning a gain region in the vicinity of the self-focal point of the shortest periodic orbit in the transverse motion. [5,6,7]. The violation of the ergodic hypothesis implied by the existence of scars is justified by various theoretical approaches [10] but remains mathematically uncer… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 33 publications
0
21
0
Order By: Relevance
“…The deformed microcavities have been experimentally realized with several different cross-sectional shapes and various materials [6-10]. Also, they become important models in the field of quantum chaos [11,12] for the study of ray-wave correspondence in open systems [13][14][15][16][17].Nonetheless, it is not easy to understand and predict the spectrum and emission directionality because the internal ray dynamics is chaotic due to the broken rotational symmetry. Therefore, many studies have concentrated on the properties of the spectrum and the role of the chaotic dynamics to generate directional light emission from high-Q WGMs.…”
mentioning
confidence: 99%
“…The deformed microcavities have been experimentally realized with several different cross-sectional shapes and various materials [6-10]. Also, they become important models in the field of quantum chaos [11,12] for the study of ray-wave correspondence in open systems [13][14][15][16][17].Nonetheless, it is not easy to understand and predict the spectrum and emission directionality because the internal ray dynamics is chaotic due to the broken rotational symmetry. Therefore, many studies have concentrated on the properties of the spectrum and the role of the chaotic dynamics to generate directional light emission from high-Q WGMs.…”
mentioning
confidence: 99%
“…It is worth mentioning that the latter geometry has also been fully studied in optical fibers over the past few years [11,12]. In particular, we experimentally demonstrated that some specific scarred modes of a chaotic optical fiber -spatially localized along the least unstable periodic orbits -can be selectively enhanced through an optical amplification process [14,20]. Moreover, as the pump absorption is clearly improved by the use of a chaotic double-clad fiber amplifier, the device has been proposed as an optimization of existing amplifiers [7,21].…”
Section: The Optical Fiber As a Versatile Optical Analogue Of A Dmentioning
confidence: 81%
“…To analyse the guided modes present in the propagating signal we calculate what we call the pseudo-time-frequency spectrum C(κ; z) in which z is the pseudo-time [31]. More precisely, C(κ; z) is obtained by the Fourier transform of the correlation function of the propagating field ψ s (r, z) with its initial condition, along a propagation length L z…”
Section: -5mentioning
confidence: 99%